1989
DOI: 10.1073/pnas.86.14.5517
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mammalian cell genetic regulation in situ by using retrovirus-derived "portable exons" carrying the Escherichia coli lacZ gene.

Abstract: Self-inactivating derivatives of Moloney murine leukemia retrovirus containing the Escherichia coli lacZ gene were used to detect and study the regulation of transcription initiated at chromosomally located promoters in mouse fibroblasts. The introduction of splice acceptor sites in all three translational reading frames relative to lacZ and the inclusion of an in-frame ATG translation start codon in one construct allowed synthesis of 13-galactosidase fusion proteins upon insertion of retrovirus vectors contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…Cloning of the DNA segment 5Ј to lacZ yielded a 8.7-kb plasmid DNA insert whose restriction map (Fig. 1A) corresponded to the chromosomal DNA region containing the retroviral construct (13). Sequence analysis showed that the distal 2 bp of the native long terminal repeat sequence of the retrovirus (Fig.…”
Section: Characterization Of Gas8 Genomic Dna and Transcripts-mentioning
confidence: 99%
See 2 more Smart Citations
“…Cloning of the DNA segment 5Ј to lacZ yielded a 8.7-kb plasmid DNA insert whose restriction map (Fig. 1A) corresponded to the chromosomal DNA region containing the retroviral construct (13). Sequence analysis showed that the distal 2 bp of the native long terminal repeat sequence of the retrovirus (Fig.…”
Section: Characterization Of Gas8 Genomic Dna and Transcripts-mentioning
confidence: 99%
“…Cells-A lacZ-containing fragment of genomic DNA from the 354 -6 cell, in which a Moloney murine leukemia virus (MoMuLV) 1 lac provirus was integrated downstream of the Gas8 genomic DNA (13), was introduced by cloning and subcloning into the pSP72NOT plasmid (Promega), yielding pGas354 -6. A series of nested deletions of this fragment was sequenced as described (14).…”
Section: Cloning and Sequencing Of Gas8 Cdna From Serum-starved Nih3t3mentioning
confidence: 99%
See 1 more Smart Citation
“…Using these kinds of vectors it would not be completely unthinkable to collect and freeze away cell lines Gossler et al (1989); (3) Kerr et al (1989); (4) Brenner et al (1989); (5) Friedrich and Soriano (1991).…”
Section: Promoter-or Gene-trappingmentioning
confidence: 99%
“…In mammals, entrapment vectors can be introduced into pluripotent ES cells in culture and then passed into the germ line via chimeras (Gossler et al 1989;Skarnes 1990). Emphasis has been placed on promoter or gene traps (Brenner et al 1989;Gossler et al 1989;Kerr et al 1989;von Melchner et al 1990;Friedrich and Soriano 1991;Reddy et al 1991) rather than on the enhancer trap vectors used in Drosophila (O'Kane and Gehring 1987;Bellen et al 1989;Bier et al 1989;Wilson et al 1989). These vectors contain a reporter gene, usually lacZ, lacking its own promoter and with or without a splice acceptor sequence upstream, and are introduced into ES cells by electroporation or via a retrovirus (Fig.…”
Section: Promoter-or Gene-trappingmentioning
confidence: 99%